A Review on Design, Synthesis and Application of Composite Materials Based on MnO2 for Energy Storage - Loukia Plakia; Ioannis A. Kartsonakis (Energies)
The design, synthesis, and application of composite materials based on manganese dioxide (MnO2) for energy storage are pivotal in advancing efficient, sustainable, and high-performance energy storage systems. The MnO2 is widely recognized for its abundance, low cost, environmental friendliness, and excellent electrochemical properties, making it a promising candidate for use in supercapacitors, batteries, fuel cells, and other energy storage systems. This study offers a comprehensive overview of how various materials influence the performance of MnO2 as an energy storage medium. Specifically, the design of composite materials is examined with respect to morphological control, integration with conductive additives, doping strategies, and structural engineering, all of which impact the final material properties. Additionally, the influence of diverse synthetic techniques—including hydrothermal synthesis, electrochemical deposition, sol–gel processing, co-precipitation, and templating methods—is evaluated. The latest attempts through which the developed composites showcase improved structural stability, inherent conductivity, and electron mobility compared to the original first material are presented in this review article. The presented results have been quite promising for the synthesis of great-performing materials with improved electrochemical data compared to that of MnO2 alone, competing with other significant energy storage materials. This review highlights future prospects for the development of state-of-the-art devices, large-scale production applications, and the use of environmentally friendly materials and methods. It is anticipated that this research will provide valuable insights to facilitate further improvements in performance and broaden the scope of practical applications in this rapidly evolving field of composite materials.